Microeconomics / Third Edition - Katz Michael L (Irwin Mcgraw-Hill, 1998)
The Market Economy, The Household, Consumer Choice, Comparative Statics and Demand, Price Changes and Consumer Welfare, The Household as Supplier, Choice Under Uncertainty, The Firm, The Firm and Its Goals, Technology and Production, Cost, The Competitive Model, The Price-Taking Firm, Equilibrium in Competitive Markets, General Equilibrium and Welfare Economics, Market Power, Monopoly, More on Price-Making Firms, Oligopoly and Strategic Behavior, Game Theory, Missing Markets, Asymmetric Information, Externalities and Public Goods, Progress Check Solutions, Appendix: An Algebraic Approach to Consumer Choice, References, Index.